Exhibition of life achievements of Mihály Mőcsényi - Bardóczi, Sándor (4D Journal of Landscape Architecture and Garden Art, 2019)
The sign MM_C can be interpreted in various ways. First of all, ‘MM’ stands for a monogram. The monogram of our beloved professor, the doyen of landscape architecture, Dr. Mihály Mőcsényi, who lived to see almost one hundred years. ‘C’ may indicate the centenary, because our professor would have reached the age of 100 this year.